Mechanism of salidroside promoting testosterone secretion induced by H2O2 in TM3 Leydig cells based on metabolomics and network pharmacology - Wang, Zixu; Xu, Yunlong; Xiong, Huazhong (Frontiers in Chemistry, 2025)
Oxidative stress-induced damage is a significant contributor to the impairment of Leydig cells in the testes, potentially diminishing the secretion of testosterone and other androgens, thereby resulting in testosterone deficiency. Salidroside, the principal bioactive constituent derived from Rhodiola, exhibits potent antioxidant properties. This study aims to investigate the underlying mechanisms by which salidroside enhances testosterone secretion. The study investigated the oxidative damage in TM3 cells induced by H2O2 and demonstrated that salidroside significantly decreased the levels of ROS and MDA, while increasing the levels of testosterone, SOD, GSH. These changes effectively ameliorated oxidative stress, mitigated oxidative damage, protected TM3 cells, and enhanced testosterone secretion. Additionally, UPLC-QE-Orbitrap-MS was employed to analyze the metabolomics of TM3 cells, identifying 28 distinct metabolites and associated metabolic pathways. Key metabolic pathways identified include Arginine biosynthesis, Alanine, aspartate and glutamate metabolism, Citrate cycle (TCA cycle), Phenylalanine metabolism, Pyruvate metabolism. Utilizing network pharmacology, the core targets of salidroside in enhancing testosterone secretion were further investigated, revealing the involvement of AMACR, CYP3A4, ECHS1, HSD17B10, MPO, and TYR. This discovery was confirmed by dry-wet analysis. To sum up, salidroside can reduce the level of oxidative stress and promote testosterone secretion through multiple metabolic pathways and multiple targets. In a word, salidroside may provide a new strategy for preventing and treating testosterone deficiency.